Planning algorithm of small cell deployment scheme - Yang LIU (Dianxin kexue)
With the rapid development of mobile network,small cell is more and more important in the construction of LTE network.A best small cell deployment scheme named association-AHP was proposed.Combining the analytic hierarchy process with the gray relational analysis method,the relationship between each deployment plan and index parameter was determined,and each plan was ranked.Finally,the best small cell deployment scheme was obtained.Simulation results indicate that association-AHP performs better than traditional algorithms in ROI,and it can improve user satisfaction.